An Analysis of Visual Social Semiotics in English Textbook - Miratul Qoriah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
The objectives of the study were (1) to analyze the embedded meanings of visual images, and (2) to analyze the suitability between visual and written messages in an English textbook entitled “Pathway to English for SMA/MA Grade X”. The approach of this study was a qualitative one by using grounded theory method. The visual images and written text were analyzed by using the descriptive framework proposed by Kress and Leeuwen (2006). This study revealed that (1) the visual images embedded three visual meanings, namely representation, interactive and composition meaning, and (2) the analysis of the visual messages, then, compared to the written messages in the texts. As the result, some messages (between visual and written messages) were suitable and others were not.